Preparation method of polyacrylonitrile film composite material with afterglow performance as well as product and application of polyacrylonitrile film composite material

By doping electron-rich TMB in the polyacrylonitrile film, using electrostatic interactions to stabilize excitons and extend the phosphorescence emission process, the problem of short afterglow life of organic long afterglow materials is solved, and the preparation of polyacrylonitrile film composite materials with high afterglow life and adjustable color is achieved.

CN119798736APending Publication Date: 2025-04-11JIANGSU XFNANO MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510007973.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The afterglow life of existing organic long afterglow materials is short and the preparation process is complex, which limits its wide application.

Method used

By doping electron-rich N4,N4,N4',N4'-tetramethyl-[1,1'-biphenyl]-4,4'-diamine (TMB) into a polyacrylonitrile (PAN) solution, the triplet exciton is stabilized by electrostatic interactions, inhibiting the active movement of the molecules, thereby prolonging the phosphorescence emission process.

Benefits of technology

It realizes long afterglow emission of polyacrylonitrile film composite material, with an afterglow life of more than 900ms, and a adjustable color, making the preparation process simple and easy to perform.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798736A_ABST
    Figure CN119798736A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a polyacrylonitrile film composite material with afterglow performance as well as a product and application thereof, and the preparation method comprises the following steps: adding TMB (Tetramethylbenzidine) into a polyacrylonitrile solution, carrying out oil bath stirring reaction, sucking the solution after the reaction is finished, dropwise casting the solution on a glass sheet, air-drying, and annealing in a drying oven to obtain the polyacrylonitrile film composite material. The polyacrylonitrile doped film with high afterglow life is prepared, the afterglow life can reach 900ms or above, the color is adjustable, and the film has light activation performance. The preparation process is simple and easy to operate, and large-scale production can be realized. The doped film prepared by the invention shows ideal machinability and nontoxicity, and meets the actual application requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic long afterglow materials and relates to a polyacrylonitrile film composite material with afterglow performance and a preparation method and application thereof. Background Art

[0002] Long afterglow materials can absorb energy under external excitation and continue to emit light after the excitation stops. Their luminescence mechanism involves a complex energy transfer process between the luminescent system and the defect system. Inorganic long afterglow materials are relatively mature, but there are some limitations, such as poor stability of sulfide-based afterglow and poor moisture resistance of silicate-based materials. Organic long afterglow materials have attracted much attention in recent years due to their diverse molecular structures, easy synthesis and processing, and adjustable colors. However, the afterglow lifetime of organic long afterglow materials is relatively short, which limits their wide application. Tang Benzhong's team proposed in Advanced Functional Materials that electron-rich organic phosphors are doped into electron-deficient polymer matrices, and the organic phosphors and polyacrylonitrile matrices are combined through attractive electrostatic interactions, which can inhibit active molecular motion, thereby allowing long-life organic room temperature phosphorescence emission. However, the selection of organic phosphorescent guests is relatively difficult, the market price is high and purification is required, making the preparation process of this type of material complicated.

[0003] Therefore, it is of great significance to develop a method for quickly and easily preparing polyacrylonitrile composite membrane materials with afterglow properties. Summary of the invention

[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing a polyacrylonitrile film composite material with afterglow performance by providing a specific host-guest doping means and a simple preparation process.

[0005] The technical problem that the present invention also solves is to provide a polyacrylonitrile film composite material prepared by the preparation method, which has a long afterglow life, adjustable color and light-activated properties.

[0006] The final technical problem to be solved by the present invention is the application of the composite material in information encryption.

[0007] Technical solution: In order to achieve the above-mentioned purpose, the present invention provides a method for preparing a polyacrylonitrile film composite material with afterglow performance, comprising the following steps: adding a TMB oil bath to a polyacrylonitrile solution and stirring the mixture at 300-500 rpm / min for reaction for 30-40 minutes; after the reaction, absorbing the solution and drop-casting it on a glass sheet; air-drying the solution and annealing it in an oven to obtain the obtained film.

[0008] The preparation method of the polyacrylonitrile solution comprises: adding DMF solution to polyacrylonitrile powder, heating and stirring until the polyacrylonitrile powder is dissolved.

[0009] The present invention further obtains a series of polyacrylonitrile doped films with different doping concentrations by changing the doping ratio of TMB to polyacrylonitrile. Photophysical test characterization is performed on the doped films with different doping concentrations to determine the optimal doping ratio. Preferably, the mass ratio of TMB to polyacrylonitrile solution is 1:80 to 1:160.

[0010] Wherein, the oil bath temperature is 90°C to 110°C.

[0011] Wherein, the annealing temperature is 120° C. to 130° C., and the annealing time is 100 to 120 minutes.

[0012] The present invention also includes a polyacrylonitrile film composite material obtained by the preparation method.

[0013] The polyacrylonitrile film composite material has a thickness of 0.2-1 mm and emits blue-green fluorescence under the irradiation of an ultraviolet lamp excitation light source.

[0014] Furthermore, the polyacrylonitrile film composite material of the present invention also has photoactivation properties.

[0015] The present invention also includes the application of the polyacrylonitrile film composite material in information encryption.

[0016] The reaction mechanism of the present invention: The present invention selects N4, N4, N4', N4'-tetramethyl-[1, 1'-biphenyl]-4, 4'-diamine (TMB) with electron-rich properties as the doping guest. Since TMB has a strong electron-donating group, it can form a spatial electrostatic interaction with the electron-withdrawing group in the polyacrylonitrile (PAN) matrix, the cyano group, to stabilize the triplet excitons and inhibit the active movement of molecules. When the luminescent system is irradiated with ultraviolet light and absorbs light energy, the light source is removed. At this time, phosphorescence emission is achieved due to the transition of molecules between different valence states. Since the above-mentioned electrostatic interaction can effectively inhibit the progress of this process, the phosphorescence emission process is prolonged, thereby achieving long afterglow emission. The polyacrylonitrile before doping is modified by nitro copolymerization to strengthen the electron-withdrawing ability of polyacrylonitrile, specifically activate the methoxy group in TMB, and the luminescent phosphor in the excited state will produce multiple split free radicals. These free radicals have a high degree of reactivity and can react chemically with other molecules, showing that the intensity of the afterglow phosphorescence of the doped film is improved after light activation. The invention realizes organic room temperature phosphorescence emission with a wide color range by adjusting the electrostatic interaction between the electron-rich phosphor and the electron-deficient PAN, thereby achieving color tunability.

[0017] Beneficial effects: Compared with the prior art, the advantages of the present invention are:

[0018] 1. The present invention prepares a polyacrylonitrile-doped film with a long afterglow lifetime, wherein the afterglow lifetime can reach more than 900ms and the color is adjustable.

[0019] 2. The preparation process of the present invention is simple, easy to operate, and can be produced on a large scale.

[0020] 3. The doped film prepared by the present invention has photoactivation properties and has phosphorescence of different intensities before and after photoactivation. Therefore, information can be encoded into a combination of phosphorescence of different light intensities, and information can be represented by a combination of weak and strong light. Therefore, it can be applied in the field of information encryption. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a picture of the prepared polyacrylonitrile film composite material taken with a camera under a T8 fluorescent lamp;

[0022] Figure 2 The state of the prepared polyacrylonitrile membrane composite material under 354nm ultraviolet excitation by a handheld ultraviolet analyzer;

[0023] Figure 3 To use a handheld UV analyzer to irradiate the polyacrylonitrile film composites with different TMB doping concentrations in a dark room environment, the camera was used to take pictures;

[0024] Figure 4 To test the single PAN fluorescence phosphorescence spectrum using a steady-state fluorescence spectrometer;

[0025] Figure 5 To test the single TMB fluorescence phosphorescence spectrum using a steady-state fluorescence spectrometer;

[0026] Figure 6 The fluorescence phosphorescence spectrum of TMB@PAN doped film with 1 mg TMB doping amount was tested using a steady-state transient fluorescence spectrometer;

[0027] Figure 7 The fluorescence phosphorescence spectrum of the TMB@PAN doped film with a TMB doping amount of 1.2 mg was tested using a steady-state transient fluorescence spectrometer;

[0028] Figure 8 The fluorescence phosphorescence spectrum of TMB@PAN doped film with 1.5mg TMB doping amount tested using steady-state transient fluorescence spectrometer;

[0029] Fig. 9 The fluorescence phosphorescence spectrum of the TMB@PAN doped film with a TMB doping amount of 1.8 mg was tested using a steady-state transient fluorescence spectrometer;

[0030] Fig.10The fluorescence phosphorescence spectrum of TMB@PAN doped film with 2mg TMB doping was tested using a steady-state transient fluorescence spectrometer;

[0031] Fig.11 To test the SSPL of TMB@PAN doped film with 1.5mg TMB doping amount under 254nm UV lamp irradiation for different time periods using steady-state transient fluorescence spectrometer;

[0032] Fig.12 The Delayed PL of TMB@PAN doped film with 1.5 mg TMB doping amount under 254 nm ultraviolet lamp irradiation for different time periods was tested using a steady-state transient fluorescence spectrometer. DETAILED DESCRIPTION

[0033] Example 1 Preparation and performance test of TMB@PAN 0.5 mm doped film with 1 mg TMB doping amount

[0034] 840 mg of polyacrylonitrile powder (purchased from MACKLIN; cas: 25014-41-9) was added to a round-bottom flask, a magnetic rod was placed and fixed on an iron stand, and placed in an oil bath. Magnetic stirring was turned on without adding solvent, 21 mL of N, N-dimethylformamide (DMF) was measured with a 25 mL syringe and slowly injected along the edge of the flask to rinse the polyacrylonitrile powder on the flask wall, and the flask was sealed with tin foil. The oil bath temperature was set to 90°C, and stirred for 30 to 40 minutes until the polyacrylonitrile was completely dissolved. At this time, 246 mg of nitrobenzene was added to raise the oil bath temperature to 110°C and continue stirring for 30 to 40 minutes. The solution was light yellow and clear oily, and the oil bath temperature was lowered to 90°C. 4 mL of polyacrylonitrile DMF solution was injected into a test tube, 1 mg of TMB was added, and a magnetic rod was placed in a 90°C oil bath and stirred for 40 minutes. The solution was drawn up with a dropper and drop-casted on a quartz glass sheet. After being evenly spread, it was air-dried for half an hour and then annealed in a forced air oven at 120°C for 100 minutes to obtain the TMB@PAN doped film.

[0035] The luminescence state was observed after irradiation for 3 min using a portable UV analyzer (purchased from Nanjing Juyou Scientific Instrument Co., Ltd.; model WFH-2048) (254 nm and 356 nm excitation light). The results are as follows: Figure 3 In the first row, it was found that the film still showed blue-green light after removing the UV light for 1s, 3s and even 5s.

[0036] The results were tested by a steady-state transient fluorescence phosphorescence spectrometer (purchased from Edinburgh Instruments; model FLS980). Figure 6 Its fluorescence phosphorescence spectrum has a fluorescence emission peak near 404nm, which is similar to the spectrum of PAN and TMB ( Figure 4 and Figure 5) comparison shows that the emission peak belongs to organic room temperature phosphorescence, and the doping of TMB causes the fluorescence spectrum of polyacrylonitrile film to red shift. Two fluorescence emission peaks appear in the 370-440nm segment of the fluorescence phosphorescence spectrum, which is the emission range of green phosphorescence, consistent with the phenomenon observed by the naked eye. At the same time, a portable UV analyzer was used to irradiate it with a 254nm UV lamp for 3 minutes, and it still showed green phosphorescence afterglow. The phosphorescence lifetime was tested using a steady-state transient fluorescence phosphorescence spectrometer, and the phosphorescence lifetime could reach 360ms.

[0037] Example 2 Preparation and performance test of TMB@PAN 0.5 mm doped film with 1.2 mg TMB doping amount

[0038] The operation steps of this example are the same as those of Example 1, except that the amount of TMB added is changed to 1.2 mg. After irradiation with a portable UV analyzer for 3 minutes and removal of the UV analyzer for 1 second, 3 seconds, or even 5 seconds, the luminescence state is similar to that of Example 1, corresponding to Figure 3 In the second row, the spectrum test shows that the fluorescence emission peak is red-shifted around 404nm, corresponding to Figure 7 In the fluorescence phosphorescence spectrum, two fluorescence emission peaks appear in the 370-440nm segment, which is the emission range of green phosphorescence, consistent with the phenomenon observed by the naked eye. After 3 minutes of ultraviolet light irradiation, the green phosphorescence afterglow is obvious and lasts for a long time. The phosphorescence lifetime is tested using a steady-state transient fluorescence phosphorescence spectrometer, and the phosphorescence lifetime can reach 616ms.

[0039] Example 3 Preparation and performance test of TMB@PAN 0.5 mm doped film with 1.5 mg TMB doping amount

[0040] The operation steps of this embodiment are the same as those of embodiment 1. After the portable UV analyzer irradiates for 3 minutes and the UV analyzer is removed for 1 second, 3 seconds, or even 5 seconds, the luminous state is similar to that of embodiment 1. Figure 3 In the third row, only the amount of TMB added was changed to 1.5 mg. The film prepared in this example is a transparent film under fluorescent light. Figure 1 , the luminescent state is stable under ultraviolet light and shows green phosphorescence. Figure 2 , the fluorescence and phosphorescence spectrum analysis shows that the fluorescence emission peak near 404nm is normal, and the green phosphorescence emission peak appears at 370-440nm. Different from other embodiments, the doped film prepared in this embodiment has only one smooth emission peak in this range, corresponding to Figure 8, indicating that the film is in a state of equilibrium of non-covalent electrostatic interaction, balancing the effective protection of triplet excitons and the normal radiative transition to ensure phosphorescence emission. After 30s of excitation light excitation, the photoactivation reaches saturation, and the afterglow lasts for up to 8s, which is a film with the best doping ratio. The phosphorescence lifetime is tested using a steady-state transient fluorescence phosphorescence spectrometer, and the phosphorescence lifetime can reach 954ms. The steady-state transient phosphorescence spectrometer is used to test the fluorescence phosphorescence spectra of the samples of this embodiment after excitation with a 254nm ultraviolet lamp in different time periods to verify the photoactivation performance of the material. As the irradiation time of the 254nm ultraviolet lamp increases, the emission peak light intensity of the steady-state fluorescence emission spectrum (SSPL) of the 1.5mg TMB@PAN doped film at 404nm decreases, and only 78% of the spectral intensity before being irradiated by the 254nm ultraviolet lamp is obtained. Fig.11 The spectral intensity of the delayed fluorescence emission spectrum (Delayed PL) increases with the extension of the excitation light irradiation time, and the spectral intensity increases by 156%. Fig.12 This fully proves the existence of photoactivation phenomenon, and it reaches saturation after 30s of excitation light irradiation.

[0041] Example 4 Preparation and performance test of TMB@PAN 0.5 mm doped film with 1.8 mg TMB doping amount

[0042] The operation steps and results of this embodiment are the same as those of embodiment 1, corresponding to Figure 3 In the fourth row, only the amount of TMB added was changed to 1.8 mg. After irradiation with a portable UV analyzer for 3 minutes and then removing the UV analyzer, the film luminescence was similar, corresponding to Fig. 9 In the fluorescence phosphorescence spectrum, two fluorescence emission peaks appear in the 370-440nm range, which is the emission range of green phosphorescence, consistent with the phenomenon observed by the naked eye. After 3 minutes of UV light irradiation, there is a green phosphorescence afterglow. The phosphorescence lifetime is tested using a steady-state transient fluorescence phosphorescence spectrometer, and the phosphorescence lifetime can reach 468ms.

[0043] Example 5 Preparation and performance test of TMB@PAN 0.5 mm doped film with 2 mg TMB doping amount

[0044] The operation steps and results of this example are the same as those of Example 1, except that the amount of TMB added is changed to 2 mg. After irradiation for 3 minutes under a portable UV analyzer and the UV analyzer is removed, the luminescence state corresponds to Fig.10 In the fluorescence phosphorescence spectrum, two fluorescence emission peaks appear in the 370-440nm range, which is the emission range of green phosphorescence, consistent with the phenomenon observed by the naked eye. After 3 minutes of UV light irradiation, green phosphorescence afterglow appears, but the afterglow effect is not as good as that of 0.5mg TMB@PAN film. The phosphorescence lifetime is tested using a steady-state transient fluorescence phosphorescence spectrometer, and the phosphorescence lifetime can reach 442ms.

[0045] Example 6 Preparation of TMB@PAN doped films of different thicknesses and performance testing

[0046] The operation steps of this embodiment are the same as those of Embodiment 3. In the film-forming stage of dripping quartz glass sheets and annealing, doped films with thicknesses of 0.2 mm, 0.5 mm, 0.8 mm, 1 mm, and 3 mm were prepared respectively. When irradiated with a 254 nm ultraviolet lamp using a portable ultraviolet analyzer, only the doped films with a thickness of less than or equal to 1 mm were observed to emit fluorescence, and no fluorescence could be observed for the doped films with a thickness of more than 1 mm.

[0047] Comparative Example 1 Preparation and Performance Test of Melamine-Replaced TMB-Doped Film

[0048] The operation steps of this comparative example are the same as those of Example 3, except that TMB is replaced by melamine. No organic room temperature phosphorescence emission can be observed under a portable UV analyzer.

[0049] Comparative Example 2 Preparation and Performance Test of Polymethyl Ether-Replaced PAN Doped Film

[0050] The operation steps of this comparative example are the same as those of Example 3, except that PAN is replaced by polymethyl ether. Under the same annealing conditions, the mixed solution cannot form a thin film on the substrate material.

[0051] Comparative Example 3 Preparation and Performance Test of PAN Doped Film Modified Without Adding Nitrobenzene

[0052] The operating steps of this comparative example are the same as those of Example 3, except that nitrobenzene is not added to prepare the TMB@PAN doped film. The steady-state transient phosphorescence spectrometer is used to test the fluorescence phosphorescence spectra of the comparative example samples after excitation by a 254nm ultraviolet lamp at different time periods to verify the photoactivation performance of the material. As the irradiation time of the 254nm ultraviolet lamp increases, the SSPL emission peak intensity of the comparative example sample remains basically unchanged, and the spectral intensity of the Delayed PL does not increase with the extension of the excitation light irradiation time, which fully proves that there is no photoactivation phenomenon in the comparative example sample.

Claims

1. A method for preparing a polyacrylonitrile film composite material with afterglow performance, characterized in that: The method comprises the following steps: adding a polyacrylonitrile solution into a TMB oil bath and stirring the mixture at a speed of 300-500 rpm / min for reaction for 30-40 minutes; after the reaction is completed, the mixture is drip-casted on a glass sheet, air-dried, and then annealed in an oven to obtain the obtained mixture.

2. The method for preparing a polyacrylonitrile film composite material with afterglow performance according to claim 1, characterized in that: The preparation method of the polyacrylonitrile solution comprises: adding N,N-dimethylformamide to polyacrylonitrile powder, heating and stirring until the polyacrylonitrile powder is dissolved.

3. The method for preparing a polyacrylonitrile film composite material with afterglow performance according to claim 1, characterized in that: The concentration of polyacrylonitrile in the polyacrylonitrile solution is 30-40 mg / mL.

4. The method for preparing a polyacrylonitrile film composite material with afterglow performance according to claim 1, characterized in that: The mass ratio of TMB to polyacrylonitrile is 1:80-1:

160.

5. The method for preparing a polyacrylonitrile film composite material with afterglow performance according to claim 1, characterized in that: The oil bath temperature is 90°C to 110°C.

6. The method for preparing a polyacrylonitrile film composite material with afterglow performance according to claim 1, characterized in that: The annealing temperature is 120-130°C, and the annealing time is 100-120 min.

7. The polyacrylonitrile film composite material obtained by the preparation method according to any one of claims 1 to 6.

8. The polyacrylonitrile film composite material according to claim 7, characterized in that: The polyacrylonitrile film composite material has a thickness of 0.2-1 mm and emits blue-green fluorescence under the irradiation of an ultraviolet lamp excitation light source.

9. Use of the polyacrylonitrile film composite material according to claim 7 or 8 in information encryption.